Yayasan UMP provides free laptops for students - Nor Salwana, Mohammad Idris (2021)
PEKAN, 16 April 2021 – Yayasan UMP provided 70 laptops to Universiti Malaysia Pahang (UMP) students in need to ease their burden in adapting to the online learning sessions.